Effect of ester compounds on biogas production: beneficial or detrimental?. Issue 1 (20th February 2014) - Yanti, Heri; Wikandari, Rachma; Millati, Ria; Niklasson, Claes; Taherzadeh, Mohammad J.
Abstract Esters are major flavor compounds in fruits, which are produced in high volume. The widespread availability of these compounds in nature attracts interest on their behavior in anaerobic digestion in waste and wastewater treatments. The aim of this work was to study the effects of various esters at different concentrations in anaerobic digestion followed by determination of their minimum inhibitory concentration (MIC), and to study the effect of chain length of functional group and alkyl chain of ester on methane production. Addition of methyl butanoate, ethyl butanoate, ethyl hexanoate, and hexyl acetate at concentration up to 5 g L−1 increased methane production, while their higher concentrations inhibited the digestion process. The MIC values for these esters were between 5 and 20 g L−1. Except hexyl acetate, the esters at concentration 5 g L−1 could act as sole carbon source during digestion. For ethyl esters, increasing number of carbon in functional group decreased methane production. For acetate esters, alkyl chain longer than butyl inhibited methane production. Effect of ester on methane production is concentration‐dependent.